2007
DOI: 10.1002/hbm.20389
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical spike‐related BOLD responses in focal epilepsy

Abstract: Till now, most studies of the Blood Oxygen Level-Dependent (BOLD) response to interictal epileptic discharges (IED) have assumed that its time course matches closely to that of brief physiological stimuli, commonly called the canonical event-related haemodynamic response function (canonical HRF). Analyses based on that assumption have produced significant response patterns that are generally concordant with prior electroclinical data. In this work, we used a more flexible model of the event-related response, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
4

Year Published

2008
2008
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 38 publications
1
58
1
4
Order By: Relevance
“…The BOLD changes appeared to take place at the epileptogenic zone, « upstream » from bilateral anterior temporal IED, which reflect propagation areas and an irritative zone with a much larger extent than the epileptogenic zone. This effect may be related to BOLD changes preceding IED as has been shown in some cases of focal epilepsy, mostly in relation to generalised IED (Hawco, et al 2007;Jacobs, et al 2009;Lemieux, et al 2008;Vaudano, et al 2009). Other studies rather suggested a "downstream" effect, with IED modulating BOLD signal and presumably neuronal activity in distant regions involved in the epileptogenic network, such as the DMN (Kobayashi, et al 2006b;) and the limbic network (Kobayashi, et al 2006a) in medial temporal epilepsy.…”
Section: Neurophysiological and Clinical Relevancementioning
confidence: 71%
“…The BOLD changes appeared to take place at the epileptogenic zone, « upstream » from bilateral anterior temporal IED, which reflect propagation areas and an irritative zone with a much larger extent than the epileptogenic zone. This effect may be related to BOLD changes preceding IED as has been shown in some cases of focal epilepsy, mostly in relation to generalised IED (Hawco, et al 2007;Jacobs, et al 2009;Lemieux, et al 2008;Vaudano, et al 2009). Other studies rather suggested a "downstream" effect, with IED modulating BOLD signal and presumably neuronal activity in distant regions involved in the epileptogenic network, such as the DMN (Kobayashi, et al 2006b;) and the limbic network (Kobayashi, et al 2006a) in medial temporal epilepsy.…”
Section: Neurophysiological and Clinical Relevancementioning
confidence: 71%
“…Modeling the residuals as an autoregressive process cannot accommodate large artifactual BOLD signal transients that coincidentally occurred during the ictal event, which may result in statistically significant non-canonical HRFs. A study on epileptic spikes revealed that most non-canonical shapes tended to occur remotely from the presumed epileptogenic focus and were likely artifacts (Lemieux et al, 2008). On the other hand, restricting the HRF to the canonical shape, such as in the standard GLM method, may prevent the detection of real activations.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Furthermore, while the canonical HRF appears to be a suitable model in normal physiological conditions (Friston et al, 1995) and for IED-related BOLD signal changes (Lemieux et al, 2008), this has not been demonstrated for seizures. Flexible modelling methods have been used, such as those based on Fourier basis sets or series of short blocks (Donaire et al, 2009;Tyvaert et al, 2009) addressing the potential complexity of ictal BOLD signal changes but they do not address the issue of how best to model these changes based on the available scalp EEG.…”
mentioning
confidence: 95%